Electrochemistry of Tin Deposition from Methanesulfonic Acid - Yuantao Yang; Junli Wang; Xuanbing Wang; Jinlong Wei; Xiaoning Tong; Ruidong Xu; Linjing Yang (Metals, 2024)
The electrolytic refining of crude tin is generally carried out in the fluorosilicic acid (H2SiF6) system with the assistance of bone glue and β-naphthol. However, the high saturated vapor pressure and low stability of H2SiF6 present environmental concerns and do not align with sustainable development goals. In this paper, the electrochemical behavior of tin on a glassy carbon (GC) electrode was studied in a relatively green and environmentally friendly methanesulfonic acid (MSA) system. Bone glue, sodium lignosulfonate, and β-naphthol were used as additives to make the deposit morphology smooth and to ensure grain refinement. The electrochemical reduction process of Sn2+ in an MSA system is a quasi-reversible process controlled by diffusion. The apparent activation energy <semantics>Ea</semantics> = 14.189 kJ/mol for the ion diffusion of Sn2+ was further calculated. The results of chronoamperometry showed that the electrocrystallization of Sn2+ on the GC electrode gradually tended to three-dimensional instantaneous nucleation with the increase in applied potential. The morphology and phase of the deposits were analyzed using scanning electron microscopy (SEM) and X-ray diffraction (XRD). The results showed that the deposits were uniform and dense pure tin. This work elucidates the electrochemical behavior of tin in a methanesulfonic acid system.